Community perspectives on gun violence and safety: The role of policing in Baltimore City. (November 2022) - Crifasi, Cassandra K.; Williams, Rebecca G.; Booty, Marisa D.; Owens-Young, Jessica L.; Webster, Daniel W.; Buggs, Shani A.L.
Abstract: Introduction: Gun violence plagues many communities that simultaneous experience other threats to their health and safety. Policing strategies to address illegal gun carrying may exacerbate or even contribute to gun violence. Methods: We conducted a mixed-methods study to understand community perspectives on gun violence, safety, and the Baltimore Police Department (BPD)'s approaches to gun violence reduction. Using an explanatory-exploratory approach – we conducted household surveys ( n  = 200) and then explored key survey findings with focus groups. Descriptive statistics were generated from the surveys and key themes were identified from the focus groups. Results: One-quarter of survey respondents reported having been a victim of a gun crime, one-third reported not feeling safe in their neighborhood, and slightly less than one-half thought police would respond quickly if shots were fired. Many participants expressed distrust in police as a result of their strategies to reduce gun carrying and address violence. Discussion: Residents in Baltimore's neighborhoods besieged by gun violence perceive the police to be ineffective in their gun violence prevention efforts. Several strategies were identified that could improve trust and reduce violence, including improving officer accountability and training, and developing tools for officers to address their own mental health and trauma. Highlights: Violence and safety concerns can impact the health and wellbeing of communities Many individuals living in areas of high crime are victimized by gun violence Police responses to address violence can harm trust and negatively impact safety